MODELING TECHNIQUES IN MOMS AND CHILDREN ON THE SUCCESS OF TOILET TRAINING AMONG TODDLER AGE CHILDREN: Toilet Training - Said, Asbath; Nurdin (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2020)
Background: The ability of children in activities related to toilets that take care of an inheritance, but something that must always be remembered and taught. To teach skills for this training, it takes the right technique or method so that it is easy to connect with children. One such technique is modeling techniques. The research objective was to determine the effect of modeling techniques on mothers and children on the success of toilet training in Toodler-aged children at PAUD AFI, Konawe Regency. Methods: Using quantitative methods through this type of pre-experimental research with a one-group approach pretest-posttest design with simple random sampling means that the sample is 30 children aged. Result: The results of the Paired T-Test explain the effect of modeling techniques on mothers and children on toilet training for toddlers in PAUD AFI, Konawe Regency (p = 0.000). . Conclusion: The use of modeling techniques in mothers and children must prepare and build from an early age for children where parents can teach children of age-related to the good toilet so that they can toilet training for children toddler.